Control algorithms for active vibration isolation systems subject to random disturbances - Abakumov, A.M.; Miatov, G.N. (Journal of sound and vibration, 2006)
Isolation from disturbances, particularly from foundations of high precision instruments, is achieved through either passive or active vibration control systems. Although a passive isolation system offers a simple and reliable means of protecting precision equipment from a vibration environment, it has performance limitations since its controllable frequency range is limited. An effective method for reducing an oscillation is by using an active vibration isolation system, which allows control of the dynamic rigidity of shock absorbers. In this paper, by considering the characteristics of the disturbing influences acting upon vibro-isolated objects, the dynamic characteristics of the AVIS device and control restriction, new optimal and quasi-optimal control algorithms are proposed. The characteristics of the new quasi-optimal active vibration isolation system proposed in the paper are investigated via experiments. It is shown that the adopted quasi-optimal active vibration isolation system can improve performance using in situ measurements.